Vibronic coupling in the ground and excited states of the imidazole radical cation - Trofimov, Alexander; Skitnevskaya, A. D.; Grigoricheva, Emma K.; Gromov, E. V.; Köppel, Horst (The journal of chemical physics, 2022)
Vibronic interactions in the ground and two excited states of the imidazole radical cation, X2A″ (π−1), A2A′ (nσ−1), and B2A″ (π−1), and the associated nuclear dynamics were studied theoretically. The results were used to interpret the recent photoelectron measurements [M. Patanen et al., J. Chem. Phys. 155, 054304 (2021)]. The present high-level electronic structure calculations employing, in particular, the single, double, and triple excitations and equation-of-motion coupled-cluster method accounting for single and double excitation approaches and complete basis set extrapolation technique for the evaluation of the vertical ionization energies of imidazole indicate that the A 2A′ and B 2A″ states are very close in energy and subject to non-adiabatic effects. Our modeling confirms the existence of pronounced vibronic coupling of the A 2A′ and B 2A″ states. Moreover, despite the large energy gap of nearly 1.3 eV, the ground state X 2A″ is efficiently coupled to the A 2A′ state. The modeling was performed within the framework of the three-state linear vibronic coupling problem employing Hamiltonians expressed in a basis of diabatic electronic states and parameters derived from ab initio calculations. The ionization spectrum was computed using the multi-configuration time-dependent Hartree method. The calculated spectrum is in good agreement with the experimental data, allowing for some interpretation of the observed features to be proposed.